Peran kecerdasan emosional dan motivasi belajar dalam membangun karakter generasi muda - Rahma, Evaneila El (Maliki Interdisciplinary Journal, 2026)
This study aims to examine the role of emotional intelligence and learning motivation in character development for the younger generation amidst global dynamics and social challenges in the digital era.Emotional intelligence and learning motivation play acentral role in determining the extent to which individuals can behave in accordance with positive character. The research method used is a qualitative approach with a literature study. The results of the analysis obtained indicate that emotional intelligence serves to provide a reference for the foundation of self-management, while intrinsic motivation plays a role in supporting learning efforts. On the other hand, extrinsic motivation plays a supporting role in efforts to build discipline. The conclusionof the study shows that the combination of emotional intelligence and learning motivation can be the key to forming the character of a resilient, adaptive, and integrated young generation. This study's recommendations emphasize strengthening and increasing synergy between families, schools, and communities in creating a harmonious environment that supports optimal emotional and motivational development.